2016
DOI: 10.1021/acs.organomet.6b00501
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactivity of Bis(protic N-heterocyclic carbene)iridium(III) Complexes

Abstract: A nonfunctionalized bis­(imidazole) ligand precursor has been directly metalated using IrCp*­(OAc)2, leading to a mixture of bis­(protic N-heterocyclic carbene) (bisPNHC) complexes (2a,b). Treatment of 2a,b with HCl gas in CH2Cl2 gave a bisPNHC complex (3a), which has been transformed into a hydride bisPNHC complex. Complex 3a underwent ligand and counterion exchange reactions to afford acetonitrile and ethylamine bisPNHC complexes (5 and 6). Furthermore, these bisPNHC complexes have been tested as catalysts i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Recently, Grotjahn demonstrated that the bis­(imidazole) 31 reacts with the acetato complex [Cp*Ir­(OAc) 2 ] to afford the bis­(pNHC) iridium­(III) complexes 32 and 33 , which can be converted quantitatively to the chlorido complex 34 upon treatment with hydrochloric acid (Scheme ). Since the positions of the nitrogen atoms in the ligand precursor are inappropriate for a cyclometalation, the bis­(pNHC) complexes 32 and 33 are most likely formed via an initial acetate-promoted C–H metalation, followed by chelation-assisted formal tautomerization. Derivatization of the chlorido complex 34 to give hydrido, nitrile, or amine complexes has also been achieved.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Grotjahn demonstrated that the bis­(imidazole) 31 reacts with the acetato complex [Cp*Ir­(OAc) 2 ] to afford the bis­(pNHC) iridium­(III) complexes 32 and 33 , which can be converted quantitatively to the chlorido complex 34 upon treatment with hydrochloric acid (Scheme ). Since the positions of the nitrogen atoms in the ligand precursor are inappropriate for a cyclometalation, the bis­(pNHC) complexes 32 and 33 are most likely formed via an initial acetate-promoted C–H metalation, followed by chelation-assisted formal tautomerization. Derivatization of the chlorido complex 34 to give hydrido, nitrile, or amine complexes has also been achieved.…”
Section: Synthesismentioning
confidence: 99%
“…39−42 The cationic bis(pNHC)iridium chlorido complex 34, as well as the hydrido complex 242, catalyzes the transfer hydrogenation of unsaturated ketones (Scheme 95). 83 While alkenones 243 are reduced to unsaturated alcohols 244, an α,β-unsaturated ketone 245 undergoes much faster reduction of the olefin bond to give the saturated ketone 246 selectively. Substrate recognition of the bis(pNHC) catalysts through hydrogen bonding is proposed to explain this notable chemoselectivity.…”
Section: Catalysts With Built-in Pnhc Ligandsmentioning
confidence: 99%
“…In literature, only few reports are listed describing counter anion effect in TH of ketones. Hou and Mazzoni groups revealed bigger counter anion played an important role while Miranda‐Soto did not detect any such effect for TH of ketone. However, to the best of our knowledge a similar effect has not been observed in TH of nitroarenes.…”
Section: Methodsmentioning
confidence: 99%
“…One important class of such ligands are the protic NHCs (pNHCs) that feature an acidic proton at one of the nitrogen atoms of the diaminoheterocycle (Figure , B ) and their deprotonated derivatives featuring a basic ring-nitrogen atom (Figure , C ). Complexes of these ligands are of particular interest to us, since they have been shown to react cooperatively together with the metal center they coordinate to activate molecules such as dihydrogen, alkynes, and even carbon dioxide . Furthermore, complexes bearing pNHCs ( B ) or C-metalated azolato ligands ( C ) have been shown to be catalytically active in the hydrogenation of polar, unsaturated bonds. , …”
Section: Introductionmentioning
confidence: 99%
“…More generalized synthetic procedures for the preparation of such complexes and a better mechanistic understanding of their reactions are still required for this field to gain traction. To date, complexes bearing C-metalated azolato ligands of type C are generally accessible via deprotonation of pNHC ligands. In addition, complexes of type C can be synthesized directly, either via the oxidative addition of the C2–X (X = halide) bond of a neutral azole to a low valent metal or via the directed C–H activation of N-donor substituted neutral azoles. ,, Less common methods for the preparation of C-azolato complexes comprise the transmetalation of lithiated azoles and the reaction of metal azido complexes with isocyanides . The C–H activation in N-donor-functionalized azoles is of interest, as this reaction resembles the orthometalation. Various mechanisms for this C–H activation have been proposed including mechanisms for the C–H activation leading to pNHC complexes .…”
Section: Introductionmentioning
confidence: 99%